2011
DOI: 10.1089/apc.2011.0149
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Unmet Need for Supportive Services for HIV Patients in Care in Los Angeles County, California

Abstract: HIV-infected patients frequently experience depression, drug use, and unstable housing but are often unable to access supportive services to manage these challenges. Data on barriers to needed supportive services are critical to improving patient access. Data from the Medical Monitoring Project (MMP), a national supplemental surveillance system for HIV-infected persons in care, was used to examine barriers to support service use and factors associated with need and unmet need for services. Interview data for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…Given the high level of unmet need for supportive services among HIVinfected individuals, further study of this type of guidance may be warranted. 26 One of the most important findings of this study was that patient concerns change over time, suggesting that interventions to support engagement in care should acknowledge this temporality and focus on promoting shifts in perspective. Without tailored intervention, individuals can get ''stuck'' at one step in the continuum.…”
Section: Discussionmentioning
confidence: 84%
“…Given the high level of unmet need for supportive services among HIVinfected individuals, further study of this type of guidance may be warranted. 26 One of the most important findings of this study was that patient concerns change over time, suggesting that interventions to support engagement in care should acknowledge this temporality and focus on promoting shifts in perspective. Without tailored intervention, individuals can get ''stuck'' at one step in the continuum.…”
Section: Discussionmentioning
confidence: 84%
“…Prior studies have shown that decreasing stigma, improving acceptance of the HIV diagnosis, and other unmet social needs will improve visit adherence. 8,9 Additionally, outreach to IDU HIV-infected patients is a priority, as they have increased risk of missed appointments and an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This is in particular relevant in case of a recent infection when VL is usually very high. Better understanding of the characteristics and needs of people living with HIV at critical steps along the HIV cascade of care is pivotal to improve responses promoting engagement with HIV care 27 28…”
Section: Discussionmentioning
confidence: 99%